1991
DOI: 10.1577/1548-8667(1991)003<0181:coamom>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Major Outer-Membrane Antigen ofEdwardsiella ictaluri

Abstract: Edwardsiella ictaluri is the cause of enteric septicemia of catfish. A monoclonal antibody (MAb AA224) was used to identify a specific and predominant outer-membrane antigen of E. ictaluri. The MAb AA224 was produced by conventional cell fusion technology with spleen cells from mice immunized with an affinity-purified antigen. The affinity-purified antigen was obtained by immunoaffinity chromatography of an E. ictaluri extract with immunoaffinity purified immunoglobin from sera of channel catfish let alums pun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Several studies have recognised the importance of OMPs for virulence of E. ictaluri and characterised the proteins for a number of isolates [16,17,19], but none have characterised the AL-93-75 isolate used in this study. Newton et al [16] first characterised OMPs from isolate ATCC 33202 and 32 other isolates on SDS-PAGE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have recognised the importance of OMPs for virulence of E. ictaluri and characterised the proteins for a number of isolates [16,17,19], but none have characterised the AL-93-75 isolate used in this study. Newton et al [16] first characterised OMPs from isolate ATCC 33202 and 32 other isolates on SDS-PAGE.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide and crude cell wall extracts from E. ictaluri (AL-93-75) were prepared according to Klesius et al [17].…”
Section: Preparations Of Whole-cell Lysates Lipopolysaccharides Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Catfish that survive an Edwardsiella ictaluri infection are generally assumed to be resistant to ESC when they recover (Klesius & Horst 1991). The bacterium is considered a good candidate for vaccine development because it has a very high serologic homogeneity (Plumb 1988, Plumb & Vinitnantharat 1989, Bertolini et al 1990), although reported efficacy using killed E. ictaluri bacterins has been equivocal at best , Saeed & Plumb 1986, Thune et al 1993, 1997b.…”
Section: Introductionmentioning
confidence: 99%